EVALUASI PRODUK SEPATU WANITA BAGI UKM KLASTIK FOOTWEAR MENGGUNAKAN METODE CHOICE BASED CONJOINT - Rizqa Amelia Zunaidi; Sinta Dewi (JURNAL REKAYASA SISTEM INDUSTRI, 2019)
In Indonesia, there are three industrial sectors with the largest number of Small Medium Enterprises (SMEs) from 2010 to 2014: food, clothing, and wood. Klastik Footwear is one of the SMEs in Indonesia that focuses on the footwear industry, especially women's shoes. Klastik Footwear brings classic and ethnic themes to its products. In order to be well received by the market, Klastik Footwear wants to identify potential consumer groups formed from market segmentation and assess the preferences of each group on Klastik Footwear products. In this study, the choice based conjoint analysis method is used to determine potential consumer preferences for Klastik Footwear products. From the results of the conjoint analysis, the importance and part-worth level of each attribute will be known. Next, a cluster and market simulator analysis is performed to see the profile of the formed segments. The results showed that there are 3 groups of potential consumers. After conducting market simulation on the three groups, it is predicted that the most ordered Klastik Footwear products by consumers are Galuh, Ara, Srikandi, and Gendhis 2 (in group 1); Brastagi, Telaga, and Gendhis 2 (in group 2); and Rinjani, Galuh, and Soko (in group 3).